Motivated to Succeed? Attitudes to Education among Native and Immigrant Pupils in England - Simon Burgess; Gabriel Heller-Sahlgren (Institute of Labor Economics (IZA), 2018)
We study attitudes to education among English adolescents. Using PISA data, we show there is considerable variation in these attitudes depending on background: immigrant students have substantially and significantly more positive attitudes to school than native children, a difference that amounts to around 0.2 standard deviations. There is no difference between first- and second-generation immigrants, and the attitude gap does not appear to depend on particular schools' policies. We also show that students in London have more positive attitudes to education on average, but this is entirely accounted for by the distribution of children of immigrants in that city.
Keywords: I21; I24; 330; education; human capital; motivation; immigrants